Foreign Direct Investment (FDI) and Its Impact on Czech Export Growth - Htoo, Theint Thinzar; Čermáková, Klára; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines the impact of foreign direct investment (FDI) inflows on manufacturing export growth in the Czech Republic, with analysis conducted in the broader context of Central and Eastern Europe (CEE) from 2000 to 2022. The study focuses on total manufacturing exports, high-technology manufacturing exports, and low-technology manufacturing exports, allowing for a sectoral and technological assessment of the FDI-export relationship. Using a panel data linear regression model with CEE countries as the reference framework, the research tests whether FDI inflows significantly influence each category of manufacturing exports, controlling for other key economic factors. The results indicate that FDI inflows have a positive and statistically significant effect on total manufacturing exports and high-technology exports, but no significant effect on low-technology exports. These findings suggest that FDI is most effective in supporting technologically advanced, capital-intensive industries and plays a limited role in traditional, low-value-added sectors. The study concludes that policies encouraging high-technology FDI, strengthening industrial capabilities, and maintaining open trade regimes can enhance the technological sophistication and competitiveness of Czech manufacturing exports, contributing to long-term structural transformation and sustainable growth.
Vedoucí práce: Klára Čermáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses